2020
DOI: 10.1016/j.buildenv.2019.106489
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into the effects of different metabolic rates of body movement on thermal comfort

Abstract: Experimental investigation into the effects of different metabolic rates of body movement on thermal comfort

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(21 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Blood flows to the exercise muscles at the beginning of the exercise to meet the energy requirements of the working muscles, and the blood vessels in the skin begin to contract, causing the skin temperature to drop. In the studies of Zhang et al [ 18 ] and Chappuis et al [ 21 ], it was observed that the core temperature decreased during the initial stage of exercise. This was consistent with our experimental results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood flows to the exercise muscles at the beginning of the exercise to meet the energy requirements of the working muscles, and the blood vessels in the skin begin to contract, causing the skin temperature to drop. In the studies of Zhang et al [ 18 ] and Chappuis et al [ 21 ], it was observed that the core temperature decreased during the initial stage of exercise. This was consistent with our experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al [ 17 ] used oral temperature and skin temperature as markers of the thermal metabolic system, and oral temperature was used as an indicator of core temperature. Zhang et al [ 18 ] used auditory canal temperature as the core temperature in the dynamic test. Zhai et al [ 19 ] and Gao et al [ 20 ] measured core temperature using telemetry pills.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the errors in the inputs to PMV (eg, metabolic rate and clothing insulation) are easy to occur. 68,69 The errors in the inputs would affect thermal neutrality determined by the PMV, which makes the thermal neutrality deviation is unable to reflect thermal adaptations around thermal neutrality fairly. For example, using the data in the study of Rajasekar and Ramachandraiah, 70 the thermal neutrality deviation is found to be 2.21 scales.…”
Section: Re Sults: C a S E S Tud Ie S For Validationmentioning
confidence: 99%
“…Zhang et al [49,50] conducted an experimental study on thermal comfort in an outdoor space with an eave in which a subject walked for 20 min and rested for 10 min at a temperature of 34 °C and relative humidity of 85 %. Fig.…”
Section: Metabolismmentioning
confidence: 99%